Goblet cell hyperplasia as a feature of neutrophilic asthma. Issue 6 (27th February 2019) - Alagha, Khuder; Bourdin, Arnaud; Vernisse, Charlotte; Garulli, Céline; Tummino, Céline; Charriot, Jérémy; Vachier, Isabelle; Suehs, Carey; Chanez, Pascal; Gras, Delphine
Summary: Background: Goblet cell hyperplasia (GCH) is a pathological finding classically reported across asthma severity levels and usually associated with smoking. Multiple biological mechanisms may contribute to excessive mucus production. Objective: We aimed to decipher the clinical meanings and biological pathways related to GCH in non‐smokers with asthma. Methods: Cough and sputum assessment questionnaire (CASA‐Q) responses at entry and 1 year later were compared to clinical and functional outcomes in 59 asthmatic patients. GCH was assessed through periodic‐acid shift (PAS) staining on endobronchial biopsies obtained at entry in a subset of 32 patients. Results: Periodic‐acid shift‐staining analysis revealed a double wave distribution discriminating patients with (>10% of the epithelial area) or without GCH. CASA‐Q scores were mostly driven by overall asthma severity ( P  < 0.0001). CASA‐Q scores remained stable at 1 year and were independently associated with BAL eosinophil content irrespective of the presence of GCH. GCH was unrelated to the presence of bronchiectasis at CT, GERD or chronic rhinosinusitis, but correlated well with neutrophilic inflammatory patterns observed upon BAL cellular analysis ( P  = 0.002 at multivariate analysis). BALF bacterial loads were unrelated to GCH or to CASA‐Q. Conclusions and Clinical Relevance: Goblet cell hyperplasia is disconnected from chronic cough and sputum when assessed by a specific questionnaire. GCH is related to neutrophilic asthma whereas symptoms are related to airway eosinophilia. The clinical counterpart of GCH is unlikely assessed by the CASA‐Q.